2013
DOI: 10.4081/aiol.2013.5345
|View full text |Cite
|
Sign up to set email alerts
|

Towards the implementation of the Water Framework Directive in Mediterranean transitional waters: the use of macroinvertebrates as biological quality elements

Abstract: During the last decade the Water Framework Directive (WFD) has driven scientific community endeavours towards the development of assessment tools to determine the Ecological Quality Status (EQS) for all surface waters, including transitional waters (TWs). Macroinvertebrates being used as Biological Quality Elements encouraged the development of distinct multimetric and multivariate indices, initially based on taxonomic approaches. Those indices were mostly developed for the marine environment and applied exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study conducted by LIUZZI & GAPPA (2008) concluded that changes in assemblage structure at the local scale were of a much smaller magnitude than those observed at regional scale and may be attributed to small differences in habitat topography, intertidal elevation, wave exposure, and distance to harbors or different sources of pollution. Invertebrates are considered very suitable organisms as indicators of natural and anthropogenic changes and there are various indices that use the ratio of sensitive and opportunistic species and groups in the assessment of the quality of coastal waters (DAUVIN & RUEL-LET, 2007;BORJA et al, 2009;CABANA et al, 2013). In the Mediterranean Sea Corallina officinalis is most commonly found in the intertidal zone, but it is also present at higher depths in subtidal area (BABBINI & BRESSAN, 1997). The mapping carried out in the eastern Adriatic has shown that settlements of this coralline algae were registered across 13% of the surveyed coastline (NIKOLIĆ et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by LIUZZI & GAPPA (2008) concluded that changes in assemblage structure at the local scale were of a much smaller magnitude than those observed at regional scale and may be attributed to small differences in habitat topography, intertidal elevation, wave exposure, and distance to harbors or different sources of pollution. Invertebrates are considered very suitable organisms as indicators of natural and anthropogenic changes and there are various indices that use the ratio of sensitive and opportunistic species and groups in the assessment of the quality of coastal waters (DAUVIN & RUEL-LET, 2007;BORJA et al, 2009;CABANA et al, 2013). In the Mediterranean Sea Corallina officinalis is most commonly found in the intertidal zone, but it is also present at higher depths in subtidal area (BABBINI & BRESSAN, 1997). The mapping carried out in the eastern Adriatic has shown that settlements of this coralline algae were registered across 13% of the surveyed coastline (NIKOLIĆ et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In many habitats, macroalgae and other flora determine the physical structure of the environment and influence the composition of organisms and their mutual interaction [14]. Various benthic groups, mostly macrofauna, have been used as indicators of different stressors or pollution in the environment [15][16][17].…”
Section: Introductionmentioning
confidence: 99%